Pembuatan Game Berbasis Kinect Sebagai Media Pembelajaran Anak Berkebutuhan Khusus (Autis) Bertema Keluarga Besarku Untuk Tingkat Sekolah Dasar - Ari Adam, Aji; , Fatah Yasin Al Irsyadi, S.T., M.T (2017)
Autism is one of the children with special needs (ABK), a birth defect and has the ability below average with compared to the normal children in general. Special schools (SLB) is an educational institution that handles the children with special needs, each SLB has a specific subject matter and teaching methods required special or different than the normal children learning methods in general. The purpose of this research is to create educational games based Kinect Xbox 360 that can assist in delivering the material, attract the children, and train the motor nerves of children, where the contents of the game by book of Autism Children Curriculum 2013 in SLB (Rumah Pintar Salatiga ), specifically for children with autism light level in Elementary School grade 2. This research is begins with visiting the Rumah Pintar SLB Salatiga and interviews by several teachers, and observed the process of teaching and learning in the SLB. The material in this game is Keluarga Besarku ,in the form of the introduction of the extended family like grandfather, grandmother, uncle and aunt which is there are game to learn to count, matching the images, compare the images, and choose the images. This game was made using the Unity 3D software, Kinect SDK, DragonBones Pro for making animation and Inscape Vector for image editing. Testing this game is done by demonstrating the game in the classroom and autism children who play the game, and during the testing was accompanied by several teachers. From the results of questionnaires that have been filled respondents stated that the game in accordance with the curriculum in special schools was the result of 79% answered agree, to see exciting game with the result 76% disagree, and be interactive with the results of 95% agreed.